2007
DOI: 10.1111/j.1365-2893.2007.00902.x
|View full text |Cite
|
Sign up to set email alerts
|

Lamivudine prevents reactivation of hepatitis B and reduces mortality in immunosuppressed patients: systematic review and meta‐analysis

Abstract: To assess the effects of prophylactic lamivudine on reactivation and mortality following immunosuppressive therapy in hepatitis B surface antigen (HBsAg)-positive patients, we performed a meta-analysis. Systematic review and meta-analysis of randomized and nonrandomized prospective controlled trials and retrospective comparative case series were identified through The Cochrane Hepato-Biliary Group Controlled Trials Register, The Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE and LILACS. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
1
11

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(94 citation statements)
references
References 76 publications
4
78
1
11
Order By: Relevance
“…[64][65][66] One meta-analysis of lamivudine for prophylaxis of HBV reactivation in immunosuppressed patients included 21 studies and showed that this drug reduced mortality. 67 The American Association for the Study of Liver Disease (AASLD), 68 the European Association for the Study of the Liver (EASL) 68 and the European Crohn and Colitis Organization (ECCO) 16 recommend early introduction of nucleoside ⁄ nucleotide analogues for all HBsAgpositive patients requiring immunosuppressive therapy. Anti-viral therapy should be administered to those patients who exhibit positive HBsAg titres with or without active viral replication.…”
Section: How Frequent Is Progression To Liver Cirrhosis In Ibd Patienmentioning
confidence: 99%
“…[64][65][66] One meta-analysis of lamivudine for prophylaxis of HBV reactivation in immunosuppressed patients included 21 studies and showed that this drug reduced mortality. 67 The American Association for the Study of Liver Disease (AASLD), 68 the European Association for the Study of the Liver (EASL) 68 and the European Crohn and Colitis Organization (ECCO) 16 recommend early introduction of nucleoside ⁄ nucleotide analogues for all HBsAgpositive patients requiring immunosuppressive therapy. Anti-viral therapy should be administered to those patients who exhibit positive HBsAg titres with or without active viral replication.…”
Section: How Frequent Is Progression To Liver Cirrhosis In Ibd Patienmentioning
confidence: 99%
“…The potential clinical consequences of hbv reactivation include liver damage from reactivation hepatitis, interruption of cancer treatment, and a mortality rate of up to 5% 7 . Prophylaxis with anti-hbv nucleoside/nucleotide analogs such as lamivudine reduces the incidence and severity of reactivation hepatitis in hbv carriers receiving chemotherapy [8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that clinical (OR= 0.09; 95% CI 0.05-0.15) and virological HBV reactivation rates (OR= 0.04; 95% CI 0.01-0.14) as well as HBV-related mortality were significantly reduced (OR= 0.20; 95% CI 0.09-0.45) in the lamivudine group. 32 In our study, group III (chronic HBV infection), two patients with HBV reactivation had neither serious reactivation nor hepatitis clinic which may be associated with their below the detectable level of HBV-DNA levels at the beginning of chemotherapy. When evaluating the reactivation phases associated with HBV, lamivudine prophylaxis may have a possible mechanism of inhibiting new hepatocytes from infection by suppressing the increase of viral replication occurring in the first phase of the reactivation and preventing hepatocyte damage associated with the reconstitution of the second phase immune system.…”
Section: Discussionmentioning
confidence: 96%